A Versatile Beam Synthesis Algorithm for Reflection Beam Formation of RIS-aided Wireless Networks - Thi Toan, Nguyen; Vu Bang Giang, Truong; Minh Tran, Nguyen (VNU Journal of Science: Computer Science and Communication Engineering; Vol 41 No 1 (2025), 2025)
Reconfigurable intelligent surfaces are emerging as a cost-effective and power-efficient solution for future wireless networks. In this paper, a gradient descent-based beam synthesis (GD-based BS) algorithm is introduced for versatile reflection beam formation in RIS-aided wireless networks. The proposed solution optimizes the reflection coefficient vector of the RIS to form one beam or multiple beams with arbitrary beamwidth and nulling points. To accomplish this task, an objective function and its gradient are derived. Then, the proposed algorithm obtains the optimal solution by iteratively updating the reflection coefficient vector using the gradient. Simulation results demonstrate that the GD-based BS algorithm effectively synthesizes arbitrary reflection beams in the tested scenarios.